2020
DOI: 10.1039/d0ja90051f
|View full text |Cite
|
Sign up to set email alerts
|

2020 atomic spectrometry update – a review of advances in X-ray fluorescence spectrometry and its special applications

Abstract: This review covers developments in and applications of XRF techniques such as EDXRF, WDXRF, TXRF, XRF microscopy using technologies such as synchrotron sources, X-ray optics, X-ray tubes and detectors in laboratory, mobile and hand-held systems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 109 publications
(108 reference statements)
0
22
0
Order By: Relevance
“…The particles were characterised for size, distribution and chemical speciation using SR-mXRF spectrometry, SR-nanoXRF spectrometry and XANES. The density of particles was estimated to be up to several 10 million per mm 3 . Titanium was detected as the metal and as TiO 2 and with Nb and a variety of other metal in the titanium implants while the particles from ceramic implants contained Zr with Cr, Fe, Hf, Sr, Y and Zn.…”
Section: Elements As Tags For Indirect Determinationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The particles were characterised for size, distribution and chemical speciation using SR-mXRF spectrometry, SR-nanoXRF spectrometry and XANES. The density of particles was estimated to be up to several 10 million per mm 3 . Titanium was detected as the metal and as TiO 2 and with Nb and a variety of other metal in the titanium implants while the particles from ceramic implants contained Zr with Cr, Fe, Hf, Sr, Y and Zn.…”
Section: Elements As Tags For Indirect Determinationsmentioning
confidence: 99%
“…1 Reviews This latest update adds to that from last year 1 and complements other reviews of analytical techniques in the series of Atomic Spectrometry Updates from the previous year. [2][3][4][5][6] Reecting the considerable interest in nanoparticles, which we have featured in previous ASUs, Galazzi et al 7 reported the application of spICP-MS, scICP-MS, LA-ICP-MS, LC-ICP-MS and FFF-ICP-MS to studies of NP biotransformation, aggregation or agglomeration, interactions with biomolecules, and the impact of these events on potential toxicity. Their review described applications of these techniques to a wide variety of clinical and plant investigations, rather than any discussion of the instrumentation involved.…”
mentioning
confidence: 99%
“…This parameter is likely related to the organic matter content of the amendment. The elements U (0), Th (0), Au (0), Se (0), Ni (0), Co (1), W (0), Sb (0), Cd (4), Pd (1), and Bi (1) were also measured, although few readings were obtained since they were below the LODs, and consequently, these were not included in the following statistical procedures. The mining mode is recommended for element concentrations greater than 10 g kg −1 .…”
Section: Field Portable X-ray Fluorescence (Pxrf) Analysismentioning
confidence: 99%
“…Portable X-ray fluorescence (pXRF) instruments and related techniques are increasingly becoming a staple of research laboratories with increasing applications in the environment, geology, cultural heritage, and soil science [1]. These instruments are quite accurate for the determination of the concentrations of elements present in moderate to high concentrations in soils [2].…”
Section: Introductionmentioning
confidence: 99%
“…Over the last few years, m-XRF has been successfully used in many applications working with multiple material types from a wide range of scientific disciplines, including the examination of geological samples to determine the mineral and element distribution in rocks (Roque ´-Rosell et al, 2017;Flude et al, 2017;van Dijk et al, 2019), in material science to study a wide range of materials and composites (Tsompopoulou & Mergia, 2013;dos Santos Pereira et al, 2017), in cultural heritage to characterize archaeological and art objects (Mantler & Schreiner, 2000;Meirer et al, 2013;Capobianco et al, 2020;Roque ´-Rosell et al, 2021;Gambardella et al, 2020), in environmental science to study soils and particulate matter (Fittschen et al, 2011), and many others (Vanhoof et al, 2020).…”
Section: Introductionmentioning
confidence: 99%